Theoretical aspects of the future teacher’s readiness for analytical activity - Timonin, Aleksandr N. (Известия Саратовского университета: Новая серия. Серия Философия. Психология. Педагогика, 2024)
Introduction. In the realities of modern society experiencing the processes of globalization and informatization, there is an increasing demand for young professionals with the skills and abilities to analyze large amounts of information, able to make decisions based on data effi ciently and quickly. Theoretical analysis. This article discusses the main features of the implementation of the analytical activity of the teacher. One of the key components of a teacher’s professional competence is analytical activity, which allows to analize, predict and evaluate the results of their work, as well as quickly respond to changes in the educational environment. Interpretations of the concept of “readiness” were analyzed, and the essence and structure of the readiness of future teachers for analytical activity were revealed. The novelty of the work lies in the revision of the structural components of the teacher’s readiness for analytical activity, corresponding to modern requirements of educational standards. The necessity of training specialists with the skills and abilities to work with data and information technologies is emphasized. Conclusion. The conclusion is formulated, according to which the formation of the future teacher’s readiness for analytical activity is a necessary factor of his or her successful professional activity, which can be carried out through the use of simulation modeling software in the educational process.